2020
DOI: 10.20448/journal.522.2020.63.556.568
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Students’ Views on the Covid-19 Distance Education Process in Music Departments of Fine Arts Faculties

Abstract: The purpose of this study is to determine evaluations and recommendations of the students, who took distance education in the spring semester of 2019-2020 in the music departments of fine arts, about this education and training process, and to develop suggestions for solving the problems experienced. In line with this purpose, the research universe is composed of music departments of fine arts faculties of universities in Turkey, and the sample consists of 1st, 2nd, 3rd and 4th grade students studying in Music… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 6 publications
1
16
0
3
Order By: Relevance
“…[2] explains that every change in the industrial revolution brings its advantages and challenges. This is emphasized by [3] that people do not want to develop themselves and do not want to change their mindset for their advancement, so that person will be left behind in all progress in this era of industrial revolution 4.0. To respond to the challenges in this 4.0 era, the writer has a desire to change himself, both in ways of thinking and in skills so that the author can be useful both for self-improvement and beneficial to many audiences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2] explains that every change in the industrial revolution brings its advantages and challenges. This is emphasized by [3] that people do not want to develop themselves and do not want to change their mindset for their advancement, so that person will be left behind in all progress in this era of industrial revolution 4.0. To respond to the challenges in this 4.0 era, the writer has a desire to change himself, both in ways of thinking and in skills so that the author can be useful both for self-improvement and beneficial to many audiences.…”
Section: Introductionmentioning
confidence: 99%
“…In the next stage, the music or message is translated by the appreciator based on the framework of the experience and knowledge of music that is owned according to the cultural conventions that become the background. [3] explains that in a music performance there can be four types of music listeners: 1) passive listeners; listeners who only hear music, enjoy music without looking for other values from the music presented or heard. Most passive listeners enjoy popular songs because, in popular songs, music lovers are more entertained by lyrics or song texts, simple melodies, stage performances, or even just the popularity of the presentation.…”
Section: Introductionmentioning
confidence: 99%
“…When the relevant literature is examined, it is seen that various studies have been carried out on distance pre-school and music education during the pandemic. Remarkably, these studies focus on the topics of information and communication technologies, especially in pre-school music education (Zhu, 2011;Panagiotakou & Pange, 2010), distance music education at the undergraduate level during the pandemic (Palau, Mogas, & Ucar, 2020;Piji Kucuk, 2020;Sakarya & Zahal, 2020, Ozer & Ustun, 2020Kesendere, Senol Sakin, & Acar, 2020;Akyurek, 2020;Bolat & Akinci, 2020), distance orchestra training in primary and secondary schools in the pandemic (Hash, 2021) and music education during the epidemic in private music courses (Aksoy, Guclu, & Nayir, 2020). In addition to these subject areas, there are various studies on distance education in the pandemic based on different disciplines (Can, 2020;Ari & Kanat, 2020;Durak, Cankaya, & Izmirli, 2020;Ozdogan & Berkant, 2020;Bakioglu & Cevik, 2020;Eti & Karaduman, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Remote learning was first announced at many colleges and universities in March 2020. As the pandemic continued, higher education leaders stated that regular education practices could not be resumed during the fall 2020 semester, leading to unprecedented courses of action for many music programs, such as the cancellation of performances and institution of remote instruction (Ozer & Ustun, 2020). As reported by Kavi (2020), these unique circumstances also changed the way marching bands operated and functioned at schools around the country.…”
mentioning
confidence: 99%
“…Other bands existed only through remote learning and virtual performances. Researchers have indicated that for many band students such modifications to normal instruction and performance may have inhibited social interaction (Ozer & Ustun, 2020). Subsequently, modifications may have been detrimental to the overall band experience because researchers have suggested that social interaction is a primary reason for students to participate in a college marching band (Carter, 2013;Cumberledge & Acklin, 2019;Heath, 2017;Wine, 2000).…”
mentioning
confidence: 99%